Epidemiology and management of gout in Taiwan: a nationwide population study - Kuo, Chang-Fu; Grainge, Matthew J.; See, Lai-Chu; Yu, Kuang-Hui; Luo, Shue-Fen; Zhang, Weiya; Doherty, Michael (BioMed Central Ltd, 2015)
INTRODUCTION: Gout is the most common inflammatory arthritis worldwide and is the only type of chronic arthritis that potentially can be ‘cured’. However, data on gout incidence, prevalence and management, assessed at multiple time points in the same population, are sparse, particularly in Asian populations. The aim of this study was to describe trends in the epidemiology of gout in the general population of Taiwan. METHODS: The National Health Insurance Research Database was used to identify patients with gout and to estimate the prevalence and incidence of gout for each calendar year from 2005 to 2010. The pattern of gout management was also examined. RESULTS: Of 23,371,362 beneficiaries in 2010, there were 1,458,569 prevalent and 56,595 incident cases of gout, giving a prevalence of 6.24% (95% confidence interval (CI), 6.23% to 6.25%) and an incidence of 2.74 (95% CI, 2.72 to 2.76) per 1,000 person-years. The annual percentage change (APC) of the standardised prevalence was −0.7% (95% CI, −1.7% to 0.3%; P = 0.14), suggesting that the prevalence of gout was essentially the same throughout the study period. However, The APC of incidence was −13.4 (95% CI, −16.1 to −10.6) between 2005 and 2007 and −2.1 (95% CI, −10.4 to 7.1) between 2007 and 2010. Regions with the highest prevalence and incidence were eastern coastal counties and offshore islets, where indigenous people are clustered. Among prevalent gout cases in 2010, only 22.93% (95% CI, 22.87% to 23.00%) were prescribed urate-lowering treatment (ULT), which remained unchanged between 2005 and 2010 at an APC of 0.0 (95% CI, −3.8 to 4.0). Uricosuric agents were more commonly prescribed than xanthine oxidase inhibitors in Taiwan. CONCLUSIONS: In Taiwan, 1 in 16 people have gout. Whereas the incidence has decreased recently, the prevalence remains unchanged. Management of gout in Taiwan is poor, with only one in five affected people being treated with ULT.